Шляхи емпіричного дослідження професійної моралі працівника органів внутрішніх справ - Котелюх, М. О.; Koteliukh, M. O.; Ларіонов, С. О.; Larionov , S. O. (Вісник Національного університету оборони України. - 2015. - Вип. 3(46). - С. 143-149, 2015)
Стаття присвячена теоретичному аналізу проблеми професійної моралі працівника органів внутрішніх справ. Визначені наукові підходи до розуміння сутності професійної моралі та професійної етики працівника ОВС. Запропоновано структурну схему професійної моралі працівника ОВС, деталізовано зміст її компонентів. Розроблено показники та критерії сформованості компонентів професійної моралі працівника ОВС.

Article is devoted to the theoretical analysis of a problem of professional morals of the employee of lawenforcement bodies. Scientific approaches to understanding of essence of professional morals and professional ethics of the employee of Department of Internal Affairs are defined. The block diagram of professional morals of the employee of Department of Internal Affairs is offered, the maintenance of its components is detailed. It is defined that components of professional morals of the employee of Department of Internal Affairs are: 1) professional moral consciousness which is shown in knowledge about appropriate professional and moral behavior, and also in regulation of own professional activity on the basis of professional and moral belief; 2) the professional and moral behavior caused by a professional and moral choice and which is realized in a professional and moral act; 3) the professional moral relation which is expressed in a professional and moral assessment of the situations connected with performance of office tasks through understanding of own professional and moral obligations and professional and moral feelings. Indicators and criteria of formation of professional morals of the employee of Department of Internal Affairs are developed.

Статья посвящена теоретическому анализу проблемы профессиональной морали сотрудника органов внутренних дел. Определены научные подходы к пониманию сущности профессиональной морали и профессиональной этики сотрудника ОВД. Предложена структурная схема профессиональной морали сотрудника ОВД, детализировано содержание её компонентов. Разработаны показатели и критерии сформированности профессиональной морали сотрудника ОВД.
Ways of empirical studying of professional morals of the employee of law-enforcement bodies
Keywords: професійна мораль; професійна етика; моральна свідомість; моральна поведінка; моральне ставлення; працівники органів внутрішніх справ; professional morals; professional ethics; moral consciousness; moral behavior; moral relation; employees of internal affairs bodies; профессиональная мораль; профессиональная этика; моральное сознание; моральное поведение; моральное отношение; работники органов внутренних дел